A Fishing‐Net‐Like 3D Host for Robust and Ultrahigh‐Rate Lithium Metal Anodes. Issue 11 (23rd February 2021) - Le, TrungHieu; Yang, Ciqing; Liang, Qinghua; Huang, Xiehe; Kang, Feiyu; Yang, Ying
Abstract: Constructing an architectural host is demonstrated to be an effective strategy for long‐life lithium metal anodes (LMAs). Herein, an integrated 3D host for stable and ultrahigh‐rate LMAs is developed by a binary highly conductive network of 2D reduced graphene oxide (rGO) and 1D carbon nanofibers (CNF) anchored with 0D ultrasmall MgZnO nanoparticles (MgZnO/CNF‐rGO). A facile net‐fishing strategy is proposed to combine the rGO nanosheets with free‐standing CNF matrix as interconnected paths for fast electron transport. Notably, serving as Li nucleation sites, the superlithiophilic MgZnO nanoparticles are uniformly distributed and tightly contacted with the conductive matrix without agglomeration due to the rGO confinement. Such a delicate nanoscale combination guarantees the effective transportation and uniform deposition of Li‐ions in the inner surface of the host. The symmetric cell of Li@MgZnO/CNF‐rGO exhibits a long lifespan above 1450 cycles under an ultrahigh current density of 50 mA cm −2 with an areal capacity of 1.0 mAh cm −2 . Impressively, it also delivers a high reversible capacity of 10 mAh cm −2 at 50 mA cm −2 . This work offers an avenue to promise the prospect for practical LMAs working under high rates and capacities. Abstract : A "net‐fishing" concept is developed to integrate 2D reduced graphene oxide and 1D carbon nanofibers anchored with 0D ultrasmall lithiophilic nanoparticles as robust host for Li metal anodes. Uniform distribution of lithiophilic seeds and tight combination with interlinked conductive scaffold enables strong bridging between smooth electron/ion transport paths, which significantly prolongs lifespan under ultrahigh current density of 50 mA cm −2 .